Feasibility of magnetic resonance imaging manual segmentation of human intercostal muscles: a morphological analysis approach - Steingruber, Laura; Ruess, Patrick; Hammer, Maria; Moll, Paul; Raab, Stephan; Koch, Marco (Frontiers in Musculoskeletal Disorders, 2026)
BackgroundIntercostal muscles (ICM) are essential for thoracic stability and respiratory mechanics. In musculoskeletal disorders and respiratory dysfunction, alterations in ICM structure and function may contribute to impaired ventilatory performance and reduced clinical capacity. Despite their physiological importance, fundamental properties of internal and external ICM fascicles—such as fascicle length, muscle volume, and interfascicular spacing—remain insufficiently described. This is mainly due to the limited spatial resolution of conventional imaging techniques such as ultrasound, computed tomography (CT), and electromyography (EMG), which cannot resolve individual ICM fascicles with sufficient detail for quantitative analysis.MethodsThis study aimed to address this gap. Eleven high-resolution thoracic T1- and T2-weighted magnetic resonance imaging (MRI) datasets were manually segmented using 3D Slicer software to characterize internal and external ICM fascicles. Standardized coronal, sagittal, and para-axial sequences were used to extract fascicle-specific parameters, including length, orientation relative to muscle course, volume, physiological cross-sectional area (PCSA), and interfascicular distance.ResultsCoronal imaging allowed reliable measurement of fascicle length and orientation for internal ICM. However, assessment of external ICM required additional para-axial sequence analysis to identify fascicle layers and attachment sites. Volumetric analysis and PCSA calculation for both internal and external ICM were feasible only through combined coronal and para-axial imaging. Results demonstrated that fascicle volume and length were proportionally related to calculated PCSA values.ConclusionManual segmentation enabled detailed physiological assessment of ICM and demonstrated both the potential and limitations of current imaging modalities. Quantification of volume, PCSA, and especially external ICM remains challenging due to the structural complexity of the thoracic wall and reliance on axial planes. Nevertheless, this study presents a practical imaging protocol for thoracic musculoskeletal assessment. It enables refined morphometric analysis using high-resolution imaging and establishes a foundation for future biomechanical modeling and individualized therapeutic approaches. Importantly, it provides the first successful example of quantitative analysis of parasternal intercostal muscle morphology in healthy individuals, forming a basis for comparative studies in patient populations with respiratory impairment.